MEMAKNAI PRAKTIK AKUNTANSI BAGI TOKO ONLINE - Zandra, Rosy Aprieza Puspita (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2018)
This study intends to examine the understanding of one of the online batik shops inPamekasan for accounting practices and their use in financial management at the batikshop "R" in Pamekasan. This research focuses on the study of reality that is formed as aresult of experience and subjective empirical views of an individual, therefore thisresearch is a qualitative study with a phenomenological approach. Based on the resultsof the study, it was discovered that the batik shop "R" only made two simple books thathad limited functions to record the flow of goods in and out, and not to record the flow offunds. In addition, it is known that the manager of the batik shop "R" has not carried outthe separation of store property and private property, as well as an obstacle that arises,namely the procedure of e-commerce transactions applied by the object opens thepossibility of delayed revenue recognition.